5(x-3)+7=4(x-1)-3

Simple and best practice solution for 5(x-3)+7=4(x-1)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-3)+7=4(x-1)-3 equation:



5(x-3)+7=4(x-1)-3
We move all terms to the left:
5(x-3)+7-(4(x-1)-3)=0
We multiply parentheses
5x-(4(x-1)-3)-15+7=0
We calculate terms in parentheses: -(4(x-1)-3), so:
4(x-1)-3
We multiply parentheses
4x-4-3
We add all the numbers together, and all the variables
4x-7
Back to the equation:
-(4x-7)
We add all the numbers together, and all the variables
5x-(4x-7)-8=0
We get rid of parentheses
5x-4x+7-8=0
We add all the numbers together, and all the variables
x-1=0
We move all terms containing x to the left, all other terms to the right
x=1

See similar equations:

| 5-3(x+2)=-4x+1 | | -2(x-17)=-20x-38 | | -2(2x-1)+3=-4x | | -11+7x=24 | | -2(b-3)-4=18 | | 5n-9-4n=0 | | 7x=10x−15 | | 6r-710=r4 | | x-34=x2 | | 2x^2-11x+17=5 | | 2t+30-t=-7 | | 2(2+3k)=2(k-6) | | Y=x3+-2x2+-11x+2 | | 8(1/4x+14)=24 | | 17x=9x−24 | | 1x+0.8=7 | | 7(x+20)=2+15(x-2) | | 2x-4=12+4x | | -3x+4-10=22 | | 3x-8x-9=36 | | 2y+10=3y-8 | | 3(4r-1)=45 | | 6x+9=5x−6,x= | | 4(-4x+2)=22x | | 2x+3=-1/2(-6-4x) | | 2/3+2n=-7 | | 4x^2+58=0 | | 12x-4=12+4x | | 8x-29=2x+31 | | -3(2a+4)=2(-3a-12) | | 22-d=5d | | -3(w+1)-w-8=4(w+4)+5 |

Equations solver categories